Proceso enseñanza aprendizaje de los fundamentos técnicos del fútbol para la captación de talentos deportivos de sexto año de la escuela de educación básica Benigno Bayancela de la ciudad de Loja, periodo 2016-2017. - Cordova Aguilera, Walter Fabricio (2018)
This research work is focused on learning the TEACHING PROCESS OF THE TECHNICAL FOUNDATION FOOTBALL FOR THE TREATMENT OF SPORTS TALENTS AT THE BASQUE EDUCATION SCHOOL BENIGNO BAYANCELA OF THE CITY OF LOJA, PERIOD 2016-2017 research raised the problem of the lack of knowledge of the technical foundations of football in sixth-year students of the School of Basic Education "Benigno Bayancela" San Cayetano neighborhood of the City of Loja, raised as a general objective, improve the interest of sixth-graders year to know the technical foundations of football in the School of Basic Education "Benigno Bayancela" San Cayetano neighborhood for the recruitment of sporting talents, reviewing the literature described in the variables: teaching-learning process, the technical foundations of football and the recruitment of sports talents, the methods used for the purposes of this research were, The deductiveinductive, global, analytical, mixed method, for the compilation of data, I base myself on the instruments of, surveys, and physical tests, where I could verify little knowledge of the technical foundations of soccer. The results obtained were excellent since it was possible to expand the knowledge in each one of the students. The discussion was made through the analysis of the data obtained, the same that when examined allowed to reach the conclusion, that the sixth year students of the School of Basic Education "Benigno Bayancela", lack of knowledge and lack of teachers to teach methodological exercises suitable for teaching the technical foundations of football.